Effects of monensin sodium and plant extracts containing cinnamaldehyde, capsicum oleoresin, and eugenol on days to puberty, gain, pregnancy rate, and feed efficiency in developing beef heifers receiving a high roughage diet - Bigler, Bo, author; Peel, Kraig, advisor; Ahola, Jason, advisor; Whittier, Jack, committee member; Holt, Tim, committee member (Colorado State University. Libraries, 2014)
To view the abstract, please see the full text of the document.
Keywords: average daily gain; beef heifers; monensin; plant extracts; puberty